1999
DOI: 10.1897/1551-5028(1999)018<0263:rsabei>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Success and Biochemical Effects in Tree Swallows (Tachycineta Bicolor) Exposed to Chlorinated Hydrocarbon Contaminants in Wetlands of the Great Lakes and St. Lawrence River Basin, Usa and Canada

Abstract: Reproduction and biochemical indicators (vitamin A, ethoxyresorufin‐O‐deethylase [EROD], highly carboxylated porphyrins) of contaminant effects, and concentrations of organochlorine residues were measured in tree swallows from wetlands within the watersheds of the Great Lakes and the St. Lawrence River, USA and Canada. To assess the vitamin A sources in the tree swallow diets, insects were collected, by ligature, from nestlings at four of these sites. Diet samples were analyzed for retinol and α‐ and β‐caroten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 25 publications
7
35
0
4
Order By: Relevance
“…The majority of studies have reported variable or no significant reproductive effects (Bishop et al 1999; Harris and Elliott 2000; McCarty and Secord 1999; Neigh et al 2006b, 2007; Thiel et al 1988), while a significant negative correlation was observed for TRES hatching success and egg concentrations on the primarily PCB-contaminated Housatonic River in Massachusetts (Custer et al 2003) and site-specific hatching success was less on the primarily TCDD-contaminated Woonasquatucket River in Rhode Island (Custer et al 2005). However, studied species along the Tittabawassee River had similar ΣPCDD/DF or TEQ WHO-Avian concentrations in eggs (Fredricks et al 2011d) to the studies on the Housatonic and Woonasquatucket rivers.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies have reported variable or no significant reproductive effects (Bishop et al 1999; Harris and Elliott 2000; McCarty and Secord 1999; Neigh et al 2006b, 2007; Thiel et al 1988), while a significant negative correlation was observed for TRES hatching success and egg concentrations on the primarily PCB-contaminated Housatonic River in Massachusetts (Custer et al 2003) and site-specific hatching success was less on the primarily TCDD-contaminated Woonasquatucket River in Rhode Island (Custer et al 2005). However, studied species along the Tittabawassee River had similar ΣPCDD/DF or TEQ WHO-Avian concentrations in eggs (Fredricks et al 2011d) to the studies on the Housatonic and Woonasquatucket rivers.…”
Section: Discussionmentioning
confidence: 99%
“…Mean concentrations at main stem sites ranged from 31.5 g/g wet weight (Holmes Road, 2000) to 100.9 (Roaring Brook, 1999). In the Great Lakes, annual average concentrations of total PCBs in tree swallow eggs were 0.5 and 1.4 g/ g wet weight at Saginaw Bay, Lake Michigan [14]; 3.2 and 4.2 g/g wet weight in lower Green Bay, Lake Michigan [3,4]; and between 0.3 and 11.1 g/g wet weight in six coastal areas of Lake Erie, Lake Ontario, and the St. Lawrence River [13,20]. Along the upper Hudson River in New York, tree swallow egg average concentrations ranged from 5.9 to 29.5 g/g wet weight [15,21].…”
Section: Total Pcbs: Exposurementioning
confidence: 99%
“…Concentrations of organochlorine chemicals and trace elements were compared among sites and years using standard statistical anal- (31) 12 (31) 18 (31) 26 (54) 32 (52) 18 (31) 40 (53) 37 (53) NS a 15 (18) 25 (38) NS 9 (20) 16 (20) 11 (35) 16 (38) 15 (32) a NS ϭ no sample; nest boxes not present at this location in 1998. yses. Numbers of eggs laid and hatching success were monitored throughout the spring and summer.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations